Using Q‐methodology to understand stakeholder perspectives on a carnivore translocation. Issue 4 (6th September 2020) - Bavin, David; MacPherson, Jenny; Denman, Huw; Crowley, Sarah L.; McDonald, Robbie A.
Abstract: Reversing global declines in predator populations is a major conservation objective, though people frequently come into conflict over carnivore conservation. As part of a national recovery programme for the pine marten Martes martes, a protected mesocarnivore in the UK, we used Q‐methodology to understand the perspectives of residents living in an area in which a pine marten translocation project was planned. In contrast to binary 'for or against' characterizations of debates surrounding such projects, we identified four perspectives with distinct priorities and concerns. A single perspective, 'Concerned Manager', opposed the translocation and marten recovery more generally, was apprehensive about impacts and favoured traditional predator management practices. Support was characterized by three perspectives: 'Environmental Protectionist', 'Natural Resource Steward' and 'Cautious Pragmatist'. Two explicitly supported the translocation but differed in their priorities: Environmental Protectionist framed marten restoration as an ethical imperative, whereas Natural Resource Steward emphasized ecological and economic benefits. Cautious Pragmatist supported marten recovery, but expressed ambivalence about the translocation. We identified areas of divergence between the four perspectives, particularly surrounding risks posed by martens and need for predator control. We identified two areas of consensus among the four perspectives: support for a biodiverse environment and translocations as a means of achieving this (though this was contingent on the species), and agreement there would be economic and ecological benefits if martens controlled non‐native grey squirrels Sciurus carolinensis . We highlight that perspectives on this project were influenced by wider issues of wildlife management and conservation, particularly the impact and management of increasing populations of another mesocarnivore, the badger Meles meles . Negative experiences and perceptions of badgers were germane to the Concerned Manager perspective, and their fear that protected status would preclude marten population control. 'Rewilding' emerged as a divisive background issue, against which some participants evaluated the translocation. In facilitating understanding of perspectives and establishing the contexts through which they were formed, we found that Q‐methodology enabled us, as a team comprising conservation practitioners and researchers, to engage meaningfully with affected residents. We recommend the tool as a useful step in assessing social feasibility of conservation translocations. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Crynodeb: Mae gwrthdroi dirywiad byd‐eang ym mhoblogaethau anifeiliaid ysglyfaethus yn un o nodau cadwraeth pennaf, er bod pobl yn aml yn dod i wrthdrawiad ynglŷn â gwarchodaeth anifeiliaid cigysol. Defnyddion ni Dull‐Q fel rhan o raglen genedlaethol ar gyfer adfer poblogaethau y bele'r coed Martes martes, anifail cigysol gwarchodedig ym Mhrydain, i ddeall safbwyntiau preswylwyr lleol mewn ardal lle cynlluniwyd prosiect trawsleoli belaod coed. Mewn cyferbyniad â disgrifiadau deuaidd o ddadleuon ynghylch a phrosiectau o'r fath fel 'o blaid neu yn erbyn', darganfyddom pedwar safbwynt gwahanol gyda blaenoriaethau a phryderon gwahanol. Roedd un safbwynt ('Rheolwr Pryderus') yn gwrthwynebu trawsleoli ac yn gwrthwynebu adfer y bele'r coed yn gyffredinol, ac yn bryderus ynghylch ag effeithiau'r trawsleoliad, ac yn ffafrio arferion traddodiadol o reoli ysglyfaethwyr. Nodweddwyd cefnogaeth gan dri safbwynt: 'Amddiffynnydd yr Amgylchedd', 'Stiward Adnoddau Naturiol' a 'Pragmatydd Pwyllog'. Fe wnaeth dau yn benodol cefnogi'r trawsleoliad ond roeddynt yn wahanol yn eu blaenoriaethau: Fe fframiodd Amddiffynnydd yr Amgylchedd adfer y bele'r coed fel rheidrwydd moesegol, tra pwysleisiodd Stiward Adnoddau Naturiol buddion ecolegol ac economaidd. Cefnogodd Pragmatydd Pwyllog adfer y bele, ond mynegodd ansicrwydd ynglŷn â'r trawsleoliad. Darganfyddom gwahaniaethau rhwng y pedwar safbwynt, yn enwedig ynghylch â'r peryglon cysylltiedig â'r belaod a'r angen am reoli ysglyfaethwyr. Roedd dau faes o gonsensws ymhlith y pedwar safbwynt: cefnogaeth am amgylchedd bioamrywiol ac am drawsleoli fel ffordd i gyflawni hyn (ond roedd hyn yn dibynnu ar y rhywogaeth), a chytundeb y byddai manteision buddiol economaidd ac ecolegol pe bai belaod yn rheoli gwiwerod llwyd Sciurus carolinensis anfrodorol. Rydym yn goleubwyntio bod materion ehangach cadwraeth a rheolaeth bywyd gwyllt wedi dylanwadu ar y safbwyntiau hyn, yn enwedig effaith a rheolaeth o boblogaethau cynyddol o anifail cigysol canolig arall, sef y mochyn daear Meles meles . O safbwynt y Rheolwr Pryderus, roedd profiadau a chanfyddiadau negyddol o foch daear yn dylanwadu ei safbwynt ar y belaod, a hefyd ar eu hofn y byddai statws gwarchodedig y bele yn atal rheoli'r boblogaeth. Mae'n amlwg bod 'ail‐wylltio' yn mater rhwygol yn y cefndir a roedd rhai cyfranogion yn mesur gwerth trawsleoliad yn ei erbyn. Wrth hybu dealltwriaeth o'r safbwyntiau a sefydlu'r cysylltau lle cawsant eu ffurfio, fe welsom fod Dull‐Q yn ein galluogi ni, fel tîm sy'n cynnwys ymarferwyr cadwraeth ac ymchwilwyr, i ymgysylltu mewn ffordd ystyrlon gyda thrigolion a fyddai'n cael eu heffeithio. Rydym yn argymell y dull fel cam defnyddiol wrth asesu'r dichonoldeb cymdeithasol o brosiectau trawsleoli cadwraethol.